Donors and archives : a guidebook for successful programs - Purcell, Aaron D., 1972- (Rowman and Littlefield, 2015)
"Donors and Archives: A Guidebook for Successful Programs highlights the importance of development and fundraising for archives, while focusing on the donor and potential donor. Their interest, their support, their enthusiasm, and their stuff are vital to the success of archival programs. Archivists involved in donor work and fundraising will find the practical advice and best practices in this book applicable, replicable, timely, and valuable"--